Current management of ovarian carcinosarcoma. Issue 2 (1st February 2007) - Mano, M. S.; Rosa, D. D.; Azambuja, E.; Ismael, G.; Braga, S.; D'HONDT, V.; Piccart, M.; Awada, A.
Abstract : Ovarian carcinosarcomas (OCS), also known as malignant mixed müllerian tumors, are uncommon malignancies that carry a poor prognosis. The presentation of OCS is usually indistinguishable from that of epithelial ovarian cancer. Due to its low frequency, prospective trials have been difficult to perform, but there is evidence that OCS are sensitive to platinum-based chemotherapy. Recent studies have shown encouraging results with platinum–ifosfamide and platinum–taxane schedules, which are usually considered the treatment of choice. However, poor performance status at presentation is also a common problem, so that many patients may be unsuitable for combination chemotherapy but may still benefit from single-agent platinum or ifosfamide or, occasionally, from nonplatinum schedules such as ifosfamide plus paclitaxel. Aggressive cytoreductive surgery appears to have a positive impact on outcome and should probably be offered to most patients. However, this procedure has been associated with higher rates of complication in OCS and should only be attempted by experienced (gynecological) surgeons in centers with expertise in the management of gynecological malignancies